Iridium ruthenium titanium composite catalyst and preparation method and application thereof

By developing iridium ruthenium titanium composite catalyst, the problem of high cost in the existing technology of high iridium use in precious metals has been solved, and higher catalytic activity and stability have been achieved, which significantly reduces the amount and cost of precious metals.

CN119530873APending Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311110586.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the existing proton exchange membrane electrolysis hydrogen production technology, the anode catalyst uses a precious metal iridium, which makes it cost high and difficult to apply on a large scale.

Method used

A iridium-ruthenium titanium composite catalyst was developed to improve the catalytic activity and stability of the catalyst by combining iridium, ruthenium and titanium elements and using specific preparation methods and complexing agents.

Benefits of technology

It achieves higher catalytic activity and stability than commercial iridium oxide catalysts, significantly reduces the amount and cost of precious metals, and has great use value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530873A_ABST
    Figure CN119530873A_ABST
Patent Text Reader

Abstract

The invention relates to an iridium-ruthenium-titanium composite catalyst and a preparation method and application thereof, the iridium-ruthenium-titanium composite catalyst comprises an iridium element, a ruthenium element and a titanium element, and an XRD spectrogram of the iridium-ruthenium-titanium composite catalyst only has an amorphous peak packet at 30-40 degrees. The iridium ruthenium titanium composite catalyst has higher catalytic activity and better stability than a commercial iridium oxide catalyst when being used as an anode catalyst for hydrogen production by water electrolysis of a proton exchange membrane, the use amount of noble metal is obviously reduced, the cost is obviously reduced, and the iridium ruthenium titanium composite catalyst has higher use value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the fields of hydrogen energy and chemical industry, and in particular, to an iridium ruthenium titanium composite catalyst and a preparation method and application thereof. Background Art

[0002] Compared with alkaline water electrolysis technology, proton exchange membrane water electrolysis hydrogen production technology has the advantages of fast response speed, high current density, wide working load range, and high hydrogen purity. In particular, it has unparalleled advantages in the field of using renewable energy to generate electricity and then electrolyze water to produce hydrogen. It is the main way to obtain green hydrogen in the future. The anode catalyst is one of the key materials for proton exchange membrane water electrolysis hydrogen production and is the main rate-controlling step for PEM water electrolysis hydrogen production. At present, commercial PEM water electrolysis devices basically use iridium oxide or iridium black catalysts, but the unit price of precious metal iridium is relatively high and the amount used in the catalyst is large, which greatly limits the large-scale application of PEM water electrolysis. Therefore, reducing the amount of anode iridium is one of the important breakthroughs for the large-scale application of PEM water electrolysis. Reducing the amount of iridium can be achieved by increasing the electrochemical intrinsic activity of the catalyst or increasing the utilization rate of the active component. Summary of the invention

[0003] The purpose of the present invention is to provide an iridium ruthenium titanium composite catalyst and a preparation method and application thereof. The iridium ruthenium titanium composite catalyst has higher catalytic activity and better stability than commercial iridium oxide catalysts, and the amount of precious metals used is significantly reduced, the cost is significantly reduced, and it has great use value.

[0004] In order to achieve the above-mentioned purpose, the first aspect of the present disclosure provides an iridium ruthenium titanium composite catalyst, which comprises iridium, ruthenium and titanium elements, and the XRD spectrum of the iridium ruthenium titanium composite catalyst only shows an amorphous peak package at 30-40°.

[0005] Optionally, the O1s characteristic peak of the XPS spectrum of the iridium ruthenium titanium composite catalyst includes a MO characteristic peak and an M-OH characteristic peak, and B0 defined by the following formula (1) is any value between 0.2 and 0.3;

[0006] B0=B1 / (B1+B2) Formula (1);

[0007] Among them, B1 is the peak area of ​​the M-OH characteristic peak in the XPS spectrum of the iridium ruthenium titanium composite catalyst, and B2 is the peak area of ​​the MO characteristic peak in the XPS spectrum of the iridium ruthenium titanium composite catalyst.

[0008] Optionally, the BET specific surface area of ​​the iridium ruthenium titanium composite catalyst is 50 to 60 m 2 / g, particle size is 2 to 10 nm.

[0009] Optionally, the chemical composition of the iridium ruthenium titanium composite catalyst is Irx Ru y Ti 1-x-y O2; wherein x is any value between 0.4 and 0.5, and y is any value between 0.1 and 0.2.

[0010] Optionally, the XRD spectrum of the iridium ruthenium titanium composite catalyst does not have crystal plane diffraction peaks of IrO2, RuO2 and TiO2.

[0011] The first aspect of the present disclosure provides a method for preparing an iridium ruthenium titanium composite catalyst, the method comprising the following steps:

[0012] S1, mixing an iridium source, a ruthenium source, a titanium source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 10, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids;

[0013] S2, separating the water in the first material to obtain an iridium ruthenium titanium composite catalyst precursor;

[0014] S3. In an oxygen-containing atmosphere, the iridium ruthenium titanium composite catalyst precursor is calcined.

[0015] Optionally, step S1 includes the following steps:

[0016] S1-1, mixing the iridium source, the first complexing agent and water for a first time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a first mixture;

[0017] S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a second mixture;

[0018] S1-3, mixing the titanium source, the third complexing agent and water for a third time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a third mixture;

[0019] S1-4, mixing the first mixture, the second mixture and the third mixture to obtain the mixed material.

[0020] Optionally, the iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or two of potassium chloroiridate and sodium chloroiridate;

[0021] The ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate;

[0022] The titanium source is a soluble salt of titanium, preferably one or both of titanyl sulfate and titanium sulfate.

[0023] Optionally, the first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate;

[0024] Preferably, the molar ratio of the first complexing agent to the iridium source is 1.5 to 2:1, preferably 1.6 to 1.8:1;

[0025] Preferably, the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1 to 2:1, preferably 1.3 to 1.6:1;

[0026] Preferably, the molar ratio of the third complexing agent to the titanium source is 1.5 to 3:1, preferably 2 to 2.5:1.

[0027] Optionally, in step S1, the molar ratio of the iridium source calculated as iridium, the titanium source calculated as titanium, and the ruthenium source calculated as ruthenium is (2-5):(1.5-5):1.

[0028] Optionally, the reaction conditions in step S1 include: temperature of 30 to 60° C., preferably 40 to 50° C.; reaction time of 1 to 4 hours, preferably 2 to 3 hours;

[0029] Preferably, in step S1, the pH of the mixed material is 6 to 7;

[0030] Optionally, a pH adjuster is added to adjust the pH; optionally, the pH adjuster is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water.

[0031] Optionally, in step S3, the conditions for the calcination treatment include: a calcination temperature of 350 to 450° C., preferably 380 to 400° C.; and a calcination time of 2 to 5 hours, preferably 3 to 4 hours.

[0032] Optionally, the method further comprises: washing the product obtained by the calcination treatment; the solvent used in the washing treatment is a mixed solution of alcohol and water, and the alcohol accounts for 10 to 95% by weight of the mixed solution, preferably 30 to 60% by weight;

[0033] Preferably, the alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol.

[0034] The third aspect of the present disclosure provides an iridium ruthenium titanium composite catalyst prepared by the method described in the second aspect of the present disclosure.

[0035] The fourth aspect of the present disclosure provides use of the iridium, ruthenium and titanium composite catalyst described in any one of the first aspect of the present disclosure or the third aspect of the present disclosure in producing hydrogen by electrolysis of water.

[0036] Through the above technical scheme, the present disclosure provides an iridium ruthenium titanium composite catalyst and a preparation method and application thereof. The iridium ruthenium titanium composite catalyst contains iridium, ruthenium and titanium elements, and only an amorphous peak package appears in the XRD spectrum, and there is no obvious crystalline diffraction peak. When used as an anode catalyst for proton exchange membrane water electrolysis to produce hydrogen, it has better stability than ruthenium catalyst, higher catalytic activity and better stability than commercial iridium oxide catalysts, and the amount of precious metals used is significantly reduced, the cost is significantly reduced, and it has great use value.

[0037] In addition, in the preparation process, the present invention uses a complexing agent to mix with the iridium source, ruthenium source and titanium source, which can improve the uniformity of the dispersion of the iridium source, ruthenium source and titanium source in the mixed solution; and the present invention uses C4-C8 organic polyacids and soluble salts thereof as complexing agents to avoid precipitation in the solution. The reaction process does not use highly corrosive solvents such as hydrochloric acid, and the preparation method is simple to operate and the conditions are mild.

[0038] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0040] Figure 1 This is the XRD pattern of the catalyst obtained in Example 1 of the present disclosure.

[0041] Figure 2 This is the TEM spectrum of the catalyst obtained in Example 1 of the present disclosure.

[0042] Figure 3 This is the O1s XPS spectrum of the catalyst obtained in Example 1 of the present disclosure. DETAILED DESCRIPTION

[0043] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0044] The first aspect of the present disclosure provides an iridium ruthenium titanium composite catalyst, which comprises iridium, ruthenium and titanium elements, and an amorphous peak package only appears at 30-40° in the XRD spectrum of the iridium ruthenium titanium composite catalyst.

[0045] The iridium ruthenium titanium composite catalyst provided by the present invention comprises iridium, ruthenium and titanium elements, and only an amorphous peak package appears in the XRD spectrum, and no obvious crystalline diffraction peak exists. When used as an anode catalyst for proton exchange membrane water electrolysis to produce hydrogen, it has higher catalytic activity and stability than commercial iridium oxide catalysts, and the amount of precious metal used is significantly reduced, and the cost is significantly reduced, so it has great use value.

[0046] In the present disclosure, "peak envelope" in the XRD spectrum refers to other forms of protrusions that appear in the XRD spectrum in addition to the obvious and sharp characteristic peaks conventionally recognized by technicians in this field. The "peak envelope" generally has the characteristics of low intensity and large width.

[0047] According to one embodiment of the present disclosure, the XRD spectrum of the iridium ruthenium titanium composite catalyst does not have the crystal plane diffraction peaks of IrO2, RuO2 and TiO2. In the iridium ruthenium titanium composite catalyst provided by the present disclosure, the iridium element, the ruthenium element and the titanium element exist in the form of amorphous oxides, and the crystal plane diffraction peaks of the three substances IrO2, RuO2 and TiO2 do not appear in the XRD spectrum.

[0048] According to one embodiment of the present disclosure, the chemical composition of the iridium ruthenium titanium composite catalyst is Ir x Ru y Ti 1-x- y O2; wherein x is any value between 0.4 and 0.5, and y is any value between 0.1 and 0.2. In the present disclosure, the chemical composition of the catalyst is determined by X-ray fluorescence analysis (XRF analysis). The chemical composition of the catalyst is consistent with the raw material addition ratio during preparation. The chemical composition described in the present disclosure is only used as a schematic representation.

[0049] According to one embodiment of the present disclosure, the O1s characteristic peak of the XPS spectrum of the iridium ruthenium titanium composite catalyst includes a MO characteristic peak and an M-OH characteristic peak, and B0 defined by the following formula (1) is any value between 0.2 and 0.3;

[0050] B0=B1 / (B1+B2) Formula (1);

[0051] Wherein, B1 is the peak area of ​​the M-OH characteristic peak of the XPS spectrum of the iridium ruthenium titanium composite catalyst, and B2 is the peak area of ​​the MO characteristic peak of the XPS spectrum of the iridium ruthenium titanium composite catalyst. The inventors have found in experiments that when the B1 / (B1+B2) ratio of the iridium ruthenium titanium composite catalyst is within the range of the present embodiment, it can have a lower overpotential, higher oxygen evolution activity, and better stability.

[0052] According to one embodiment of the present disclosure, the BET specific surface area of ​​the iridium ruthenium titanium composite catalyst is 50 to 60 m 2 / g, and the particle size is 2 to 10 nm, preferably 3 to 6 nm. In the present disclosure, the particle size of the catalyst particles refers to the particle size of the catalyst particles measured by transmission electron microscopy. For example, "the particle size of the catalyst particles is 2 to 10 nm" means that the particle size of each particle in the transmission electron microscopy spectrum of the catalyst particles is within the range of 2 to 10 nm.

[0053] A second aspect of the present disclosure provides a method for preparing an iridium ruthenium titanium composite catalyst, the method comprising the following steps:

[0054] S1, mixing an iridium source, a ruthenium source, a titanium source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 10, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids;

[0055] S2, separating the water in the first material to obtain an iridium ruthenium titanium composite catalyst precursor;

[0056] S3. In an oxygen-containing atmosphere, the iridium ruthenium titanium composite catalyst precursor is calcined.

[0057] According to an embodiment of the present disclosure, step S1 includes the following steps:

[0058] S1-1, mixing the iridium source, the first complexing agent and water for a first time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a first mixture;

[0059] S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a second mixture;

[0060] S1-3, mixing the titanium source, the third complexing agent and water for a third time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a third mixture;

[0061] S1-4, mixing the first mixture, the second mixture and the third mixture to obtain the mixed material. The above implementation can improve the uniformity of the dispersion of the iridium source, the ruthenium source and the titanium source in the mixed material; at the same time, precipitation in the solution can be avoided; the reaction process does not use highly corrosive solvents such as hydrochloric acid, providing a preparation method that is easy to operate and has mild conditions.

[0062] According to one embodiment of the present disclosure, the iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or two of potassium chloroiridate and sodium chloroiridate;

[0063] The ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate;

[0064] The titanium source is a soluble salt of titanium, preferably one or both of titanyl sulfate and titanium sulfate.

[0065] According to one embodiment of the present disclosure, the first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate;

[0066] Preferably, the molar ratio of the first complexing agent to the iridium source is 1.5 to 2:1, preferably 1.6 to 1.8:1;

[0067] Preferably, the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1 to 2:1, preferably 1.3 to 1.6:1;

[0068] Preferably, the molar ratio of the third complexing agent to the titanium source is 1.5 to 3: 1, preferably 2 to 2.5: 1. The above embodiment can avoid precipitation in the solution, and is conducive to the catalyst having a lower overpotential, higher oxygen evolution activity and better stability.

[0069] According to an embodiment of the present disclosure, in step S1, the molar ratio of the iridium source calculated as iridium, the titanium source calculated as titanium, and the ruthenium source calculated as ruthenium is (2-5): (1.5-5): 1. The above embodiment is conducive to the catalyst having a lower overpotential, higher oxygen evolution activity, and better stability.

[0070] According to one embodiment of the present disclosure, the reaction conditions in step S1 include: a temperature of 30 to 60° C., preferably 40 to 50° C.; a reaction time of 1 to 4 hours, preferably 2 to 3 hours;

[0071] Preferably, in step S1, the pH of the mixed material is 6 to 7;

[0072] Optionally, a pH adjuster is added to adjust the pH; optionally, the pH adjuster is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water.

[0073] According to an embodiment of the present disclosure, in step S3, the conditions of the calcination treatment include: a calcination temperature of 350 to 450°C, preferably 380 to 400°C; and a calcination time of 2 to 5 hours, preferably 3 to 4 hours. The above embodiment is conducive to the catalyst having a lower overpotential, higher oxygen evolution activity, and better stability.

[0074] According to an embodiment of the present disclosure, the method further comprises: washing the product obtained by the roasting treatment; the solvent used in the washing treatment is a mixed solution of alcohol and water, the alcohol accounts for 10 to 95% by weight of the mixed solution, preferably 30 to 60% by weight; preferably, the alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol. In the above preferred embodiment, it is easier to separate the catalyst by centrifugation.

[0075] The third aspect of the present disclosure provides an iridium ruthenium titanium composite catalyst prepared by the method described in the second aspect of the present disclosure.

[0076] The fourth aspect of the present disclosure provides use of the iridium, ruthenium and titanium composite catalyst described in any one of the first aspect of the present disclosure or the third aspect of the present disclosure in producing hydrogen by electrolysis of water.

[0077] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0078] The raw materials used in the examples were all commercially available and were analytically pure unless otherwise specified. Chloroiridic acid or alkali metal chloroiridic acid salt was prepared as an aqueous solution with a concentration of 0.182 mol / L for use, or a solution with a higher concentration for use. The purity of titanium sulfate was 96% by weight, and the rest were analytically pure.

[0079] Instruments, methods and conditions for TEM analysis: The model of the high-resolution transmission electron microscope (HRTEM) used in the present invention is JEM-2100 (HRTEM) (Japan Electron Co., Ltd.), and the test conditions of the high-resolution transmission electron microscope are: the acceleration voltage is 200 kV.

[0080] The model of the X-ray fluorescence spectrometer (XRF) is Rigaku 3013 X-ray fluorescence spectrometer, and the X-ray fluorescence spectrometry analysis test conditions are: scanning time is 100 s, and the atmosphere is air.

[0081] The present disclosure detects the elements on the surface of the material by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy used is an ESCALab220i-XL X-ray electron spectrometer equipped with Avantage V5.926 software produced by VG Scientific. The X-ray photoelectron spectroscopy analysis test conditions are as follows: the excitation source is monochromatic A1Kα X-ray, the power is 330W, and the basic vacuum during the analysis test is 3×10 -9 In addition, the electron binding energy was calibrated using the C1s peak (284.3 eV) of elemental carbon.

[0082] BET test method: In the present disclosure, the pore structure properties of the samples were measured by a Quantachrome AS-6B analyzer, and the specific surface area of ​​the catalyst was obtained by the Brunauer-Emmett-Taller (BET) method.

[0083] X-ray diffraction analysis (XRD) was carried out on a Shimadzu XRD-6000 X-ray diffractometer, Japan, with the test conditions including: tube voltage 40 kV, tube current 40 mA, Cu target Kα radiation, and 2θ scanning range of 5° to 80°.

[0084] The electrochemical workstation model is PARSTAT3000A-DX, and the rotating disk electrode model is 636A. A three-electrode system is used, with a saturated calomel electrode as the reference electrode, a platinum sheet as the counter electrode, and a glassy carbon electrode as the working electrode. The electrolyte used under acidic conditions is a 0.5M H2SO4 solution. The catalyst to be tested is ultrasonically dispersed uniformly in a mixed solution of isopropanol, water, and Nafion, and then dripped onto the surface of the glassy carbon electrode. After natural drying, the working electrode is obtained. The catalyst loading is 0.38 mg cm -2 The test temperature was 25°C. Oxygen was passed through the solution for 30 minutes before the test to saturate the solution with oxygen. The rotation speed was 2500rpm. The scanning range of the linear polarization curve was 1.2-1.5V (vs RHE) and the scanning rate was 5mV / s. The scanning range of the stability test was 1.26V-1.56V (vs RHE), the scanning rate was 50mV / s, and the number of scanning circles was 10,000.

[0085] Example 1 Catalyst Ir 0.5 Ru 0.1 Ti 0.4 Preparation of O2

[0086] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 1.05 g (5.47 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 6 and 7; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;

[0087] (2) weighing 0.15 g (0.73 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.16 g (0.83 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 6 and 7; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1.1:1;

[0088] (3) Weigh 0.73 g (2.92 mmol) of titanium sulfate and dissolve it in 10 ml of water, weigh 0.84 g (4.38 mmol) of citric acid, stir and mix at room temperature, and adjust the pH of the solution to between 6 and 7; wherein the molar ratio of the third complexing agent to the titanium source in terms of titanium is 2.5:1; and the molar ratio of the iridium source in terms of iridium, the titanium source in terms of titanium, and the ruthenium source in terms of ruthenium is 5:4:1.

[0089] (4) mixing the three solutions of steps (1) to (3) and reacting them at 50° C. for 2 h;

[0090] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;

[0091] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 370°C at a rate of 2°C / min and maintained for 3 h;

[0092] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube with the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-1.

[0093] XRF test analysis shows that the chemical composition of CAT-1 is Ir 0.5 Ru 0.1 Ti 0.4 O2. The XRD pattern of CAT-1 is as follows Figure 1 As shown in the figure, it can be seen that only weak amorphous peaks appear near 34° and 40°. TEM test analysis shows that the particle size of CAT-1 is 2 to 5 nm.

[0094] Example 2 Catalyst Ir 0.4 Ru 0.1 Ti 0.5 Preparation of O2

[0095] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 1.05 g (5.47 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 6 and 7; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;

[0096] (2) Weighing 0.19 g (0.92 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.20 g (1.04 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1.1:1;

[0097] (3) Weigh 1.14 g (4.56 mmol) of titanium sulfate and dissolve it in 10 ml of water, weigh 1.40 g (7.29 mmol) of citric acid, stir and mix at room temperature, and adjust the pH of the solution to between 7 and 8; wherein the molar ratio of the third complexing agent to the titanium source in terms of titanium is 1.6:1; and the molar ratio of the iridium source in terms of iridium, the titanium source in terms of titanium, and the ruthenium source in terms of ruthenium is 4:5:1.

[0098] (4) mixing the three solutions of steps (1) to (3) and reacting them at 40° C. for 1 h;

[0099] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;

[0100] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 370°C at a rate of 2°C / min and maintained for 3 h;

[0101] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detected neutral), and place the centrifuge tube with the catalyst in a forced air drying oven (60°C) for 12 h to finally obtain the catalyst, which was recorded as CAT-2.

[0102] XRF test analysis shows that the chemical composition of CAT-2 is Ir 0.4 Ru 0.1 Ti 0.5 O2.

[0103] Example 3 Catalyst Ir 0.4 Ru 0.2 Ti 0.4 Preparation of O2

[0104] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 1.05 g (5.47 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1.5:1;

[0105] (2) weighing 0.38 g (1.83 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.36 g (1.88 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 7 and 8; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1:1;

[0106] (3) Weigh 0.91 g (3.64 mmol) of titanium sulfate and dissolve it in 10 ml of water, weigh 1.40 g (7.29 mmol) of citric acid, stir and mix at room temperature, and adjust the pH of the solution to between 7 and 8; wherein the molar ratio of the third complexing agent to the titanium source in terms of titanium is 2:1; and the molar ratio of the iridium source in terms of iridium, the titanium source in terms of titanium, and the ruthenium source in terms of ruthenium is 2:2:1.

[0107] (4) mixing the three solutions of steps (1) to (3) and reacting them at 40° C. for 1 h;

[0108] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;

[0109] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 370°C at a rate of 2°C / min and maintained for 2 h.

[0110] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detected neutral), and place the centrifuge tube with the catalyst in a forced air drying oven (60°C) for 12 h to finally obtain the catalyst, which was recorded as CAT-3.

[0111] XRF test analysis shows that the chemical composition of CAT-3 is Ir 0.4 Ru 0.2 Ti 0.4 O2.

[0112] Example 4 Catalyst Ir 0.5 Ru 0.1 Ti 0.4 Preparation of O2

[0113] The catalyst was prepared by the same method as in Example 1, except that:

[0114] The iridium source in step (1) is replaced with potassium chloroiridate, and the complexing agent is replaced with tartaric acid, and the number of moles added is the same as in Example 1;

[0115] The ruthenium source in step (2) is replaced with ruthenium acetate, and the complexing agent is replaced with malic acid, and the number of moles added is the same as in Example 1;

[0116] The titanium source in step (3) is replaced with titanyl sulfate, and the complexing agent is replaced with succinic acid, and the number of moles added is the same as in Example 1;

[0117] The calcination conditions in step (6) were adjusted to: heating to 380° C. at a heating rate of 2° C. / min for 2 h. The remaining processes were the same as in Example 1. The obtained catalyst product was recorded as CAT-4.

[0118] XRF test analysis shows that the chemical composition of CAT-4 is Ir 0.5 Ru 0.1 Ti 0.4 O2.

[0119] Example 5 Catalyst Ir 0.5 Ru 0.1 Ti 0.4 Preparation of O2

[0120] The catalyst was prepared by the same method as in Example 1, except that:

[0121] The amount of citric acid in step (1) is 1.19 g (6.20 mmol); wherein the molar ratio of the first complexing agent to the iridium source is 1.7:1;

[0122] The amount of citric acid in step (2) is 0.21 g (1.09 mmol); wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 1.5:1;

[0123] The weighed amount of citric acid in step (3) is 1.23 g (6.41 mmol); wherein the molar ratio of the third complexing agent to the titanium source calculated as titanium is 2.2:1; the molar ratio of the iridium source calculated as iridium, the titanium source calculated as titanium and the ruthenium source calculated as ruthenium is 5:4:1.

[0124] XRF test analysis shows that the chemical composition of CAT-5 is Ir 0.5 Ru 0.1 Ti 0.4 O2.

[0125] Example 6 Catalyst Ir 0.5 Ru 0.1 Ti 0.4 Preparation of O2

[0126] (1) taking 20 mL (3.64 mmol) of chloroiridic acid aqueous solution, weighing 0.70 g (3.64 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 6 and 7; wherein the molar ratio of the first complexing agent to the iridium source in terms of iridium is 1:1;

[0127] (2) weighing 0.15 g (0.73 mmol) of ruthenium trichloride and dissolving it in 5 ml of water, weighing 0.10 g (0.51 mmol) of citric acid, stirring and mixing at room temperature, and adjusting the pH of the solution to between 6 and 7; wherein the molar ratio of the second complexing agent to the ruthenium source in terms of ruthenium is 0.7:1;

[0128] (3) Weigh 0.73 g (2.92 mmol) of titanium sulfate and dissolve it in 10 ml of water, weigh 0.67 g (4.38 mmol) of citric acid, stir and mix at room temperature, and adjust the pH of the solution to between 6 and 7; wherein the molar ratio of the third complexing agent to the titanium source in terms of titanium is 1.2:1; and the molar ratio of the iridium source in terms of iridium, the titanium source in terms of titanium, and the ruthenium source in terms of ruthenium is 5:4:1.

[0129] (4) mixing the three solutions of steps (1) to (3) and reacting them at 50° C. for 2 h;

[0130] (5) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;

[0131] (6) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 370°C at a rate of 2°C / min and maintained for 3 h;

[0132] (7) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube with the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-6.

[0133] XRF test analysis shows that the chemical composition of CAT-6 is Ir 0.5 Ru 0.1 Ti 0.4 O2.

[0134] Example 7 Catalyst Ir 0.3 Ru 0.3 Ti 0.4 Preparation of O2

[0135] The same preparation method as in Example 1 was used, except that:

[0136] The molar ratio of the iridium source calculated as iridium, the titanium source calculated as titanium and the ruthenium source calculated as ruthenium is 1:1.3:1; the aqueous solution of chloroiridic acid weighed in step (1) is 20 mL (3.64 mmol); the ruthenium trichloride weighed in step (2) is 0.75 g (3.64 mmol); the titanium sulfate weighed in step (3) is 6.48 g (4.73 mmol); the obtained catalyst product is recorded as CAT-7.

[0137] XRF test analysis shows that the chemical composition of CAT-7 is Ir 0.3 Ru 0.3 Ti 0.4 O2.

[0138] Example 8 Catalyst Ir 0.5 Ru 0.1 Ti 0.4 Preparation of O2

[0139] The same preparation method as in Example 1 was used, except that:

[0140] The calcination reaction conditions in step (6) are: calcination temperature is 500° C., and reaction time is 1 h. The obtained catalyst product is recorded as CAT-8.

[0141] XRF test analysis shows that the chemical composition of CAT-8 is Ir 0.5 Ru 0.1 Ti 0.4 O2.

[0142] Example 9 Catalyst Ir 0.5 Ru 0.1 Ti 0.4 Preparation of O2

[0143] The same preparation method as in Example 1 was used, except that:

[0144] In step (1), step (2) and step (3), the pH of the solution is adjusted to 8 to 9. The obtained catalyst product is recorded as CAT-9.

[0145] XRF test analysis shows that the chemical composition of CAT-9 is Ir 0.5 Ru 0.1 Ti 0.4 O2.

[0146] Example 10 Catalyst Ir 0.5 Ru 0.1 Ti 0.4 Preparation of O2

[0147] The same preparation method as in Example 1 was used, except that:

[0148] (1) Take 20 mL (3.64 mmol) of aqueous chloroiridic acid solution, take 0.15 g (0.73 mmol) of ruthenium trichloride and dissolve it in 5 ml of water, take 0.73 g (2.92 mmol) of titanium sulfate and dissolve it in 10 ml of water, weigh 2.05 g (10.68 mmol) of citric acid, stir and mix at room temperature, and adjust the pH of the solution to between 6 and 7; the molar ratio of the iridium source calculated as iridium, the titanium source calculated as titanium and the ruthenium source calculated as ruthenium is 5:4:1.

[0149] (2) reacting the mixed solution of step (1) at 50° C. for 2 h;

[0150] (3) After cooling, spin-dry at 70°C and dry in an oven at 120°C for 8 h;

[0151] (4) After the catalyst is taken out and cooled, it is ground and laid flat on a porcelain boat. In an air atmosphere, the temperature is increased to 370°C at a heating rate of 2°C / min and maintained for 3 h;

[0152] (5) Cool to room temperature, add a certain amount of deionized water for ultrasonic washing and centrifugation (10000 rpm, 10 min), then wash with a 1:1 mixed solvent of ethanol and water and centrifuge for 3 times (pH test paper detection is neutral), and place the centrifuge tube with the catalyst in a forced air drying oven (60°C) for 12 h. The obtained catalyst product is recorded as CAT-10.

[0153] XRF test analysis shows that the chemical composition of CAT-10 is Ir 0.5 Ru 0.1 Ti 0.4 O2.

[0154] Comparative Example 1

[0155] Commercial iridium dioxide catalyst was purchased from Sigma Aldrich Company with product number 206237 and was recorded as D1.

[0156] Comparative Example 2

[0157] The catalyst was prepared by the same method as in Example 1, except that:

[0158] No citric acid complexing agent is added in steps (1) to (3), and the other processes are the same as in Example 1; the obtained catalyst product is recorded as D2.

[0159] XRF analysis showed that the chemical composition of D2 is Ir 0.5 Ru 0.1 Ti 0.4 O2.

[0160] The catalyst particle size, BET specific surface area, B0 (M-OH / (M-OH+MO)) and electrochemical performance test data (initial overpotential, mV, denoted as G1; final overpotential, mV, denoted as G2; the difference between the final overpotential and the initial overpotential, G2-G1, mV; test current density 10 mA / cm 2 , Initial mass specific activity of the catalyst at 1.45 V vs. RHE, A / g (Ir+Ru) , denoted as M) are listed in the following Table 1.

[0161] Table 1

[0162]

[0163] According to the data in Table 1, we can see that:

[0164] Compared with catalysts D1 to D2 in comparative examples 1 to 2, catalysts CAT-1 to CAT-10 prepared by the method provided in the present invention have lower overpotential G1 and higher mass specific activity M, indicating that CAT-1 to CAT-10 have higher oxygen evolution activity and better stability. The catalyst prepared in the present invention uses less precious metal and has low cost.

[0165] Compared with D2 (no complexing agent was added during the preparation process), the particle size of CAT-1 to CAT-10 is significantly smaller than that of D2, indicating that the addition of a complexing agent during the preparation process of the present disclosure can effectively improve the dispersion of the raw materials and reduce the particle size of the catalyst particles.

[0166] By comparing CAT-1 and CAT-6, it can be seen that within the molar ratio of the first complexing agent to the iridium source calculated in iridium, the molar ratio of the second complexing agent to the ruthenium source calculated in ruthenium, and the molar ratio of the third complexing agent to the titanium source calculated in titanium, CAT-1 has a larger B0 value, a lower overpotential G1, a higher mass specific activity M, and a smaller value of G2-G1, indicating that CAT-1 has a higher oxygen evolution activity and better stability.

[0167] By comparing CAT-1 and CAT-7, it can be seen that within the molar ratio range of the iridium source calculated in iridium, the titanium source calculated in titanium and the ruthenium source calculated in ruthenium disclosed in the present invention, CAT-1 has a smaller particle size, a lower overpotential G1, a higher mass specific activity M, and a smaller value of G2-G1, indicating that CAT-1 has a higher oxygen evolution activity and better stability.

[0168] By comparing CAT-1 and CAT-8, it can be seen that within the calcination temperature and calcination time range disclosed in the present invention, CAT-1 has a smaller particle size, a lower overpotential G1, and a higher mass specific activity M, indicating that CAT-1 has a higher oxygen evolution activity.

[0169] By comparing CAT-1 and CAT-9, it can be seen that within the preferred pH range of the present disclosure, CAT-1 has a larger B0 value, a lower overpotential G1, a higher mass specific activity M, and a smaller value of G2-G1, indicating that CAT-1 has a higher oxygen evolution activity and better stability.

[0170] By comparing CAT-1 and CAT-10, it can be seen that under the preferred material mixing order of the present invention, CAT-1 has a smaller particle size, a lower overpotential G1, a higher mass specific activity M, and a smaller value of G2-G1, indicating that CAT-1 has a higher oxygen evolution activity and better stability.

[0171] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0172] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0173] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. An iridium ruthenium titanium composite catalyst, characterized in that: The iridium ruthenium titanium composite catalyst contains iridium, ruthenium and titanium elements, and the XRD spectrum of the iridium ruthenium titanium composite catalyst only shows an amorphous peak package at 30-40 degrees.

2. The iridium ruthenium titanium composite catalyst according to claim 1, wherein The O1s characteristic peak of the XPS spectrum of the iridium ruthenium titanium composite catalyst includes a MO characteristic peak and an M-OH characteristic peak, and B0 defined by the following formula (1) is any value between 0.2 and 0.3; B0=B1 / (B1+B2) Formula (1); Among them, B1 is the peak area of ​​the M-OH characteristic peak in the XPS spectrum of the iridium ruthenium titanium composite catalyst, and B2 is the peak area of ​​the MO characteristic peak in the XPS spectrum of the iridium ruthenium titanium composite catalyst.

3. The iridium ruthenium titanium composite catalyst according to claim 1, wherein The BET specific surface area of ​​the iridium ruthenium titanium composite catalyst is 50 to 60 m 2 / g, particle size is 2 to 10 nm.

4. The iridium ruthenium titanium composite catalyst according to claim 1, wherein The chemical composition of the iridium ruthenium titanium composite catalyst is Ir x Ru y Ti 1-x-y O2; wherein x is any value between 0.4 and 0.5, and y is any value between 0.1 and 0.

2.

5. The iridium ruthenium titanium composite catalyst according to claim 1, wherein The XRD spectrum of the iridium, ruthenium and titanium composite catalyst does not have crystal plane diffraction peaks of IrO2, RuO2 and TiO2.

6. A method for preparing an iridium ruthenium titanium composite catalyst, characterized in that: The method comprises the following steps: S1, mixing an iridium source, a ruthenium source, a titanium source, a complexing agent and water, and reacting the resulting mixture to obtain a first material; wherein the pH of the mixture is 5 to 10, and the complexing agent is selected from C4 to C8 organic polyacids and soluble salts of C4 to C8 organic polyacids; S2, separating the water in the first material to obtain an iridium ruthenium titanium composite catalyst precursor; S3. In an oxygen-containing atmosphere, the iridium ruthenium titanium composite catalyst precursor is calcined.

7. The method according to claim 6, wherein: Step S1 includes the following steps: S1-1, mixing the iridium source, the first complexing agent and water for a first time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a first mixture; S1-2, mixing the ruthenium source, the second complexing agent and water for a second time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a second mixture; S1-3, mixing the titanium source, the third complexing agent and water for a third time and adjusting the pH to 5 to 10, preferably 6 to 7, to obtain a third mixture; S1-4, mixing the first mixture, the second mixture and the third mixture to obtain the mixed material.

8. The method according to claim 7, wherein: The iridium source is selected from one or more of chloroiridic acid and chloroiridic acid alkali metal salts; preferably, the chloroiridic acid alkali metal salt is selected from one or two of potassium chloroiridate and sodium chloroiridate; The ruthenium source is a soluble salt of ruthenium, preferably one or both of ruthenium trichloride and ruthenium acetate; The titanium source is a soluble salt of titanium, preferably one or both of titanyl sulfate and titanium sulfate.

9. The method according to claim 7, wherein: The first complexing agent, the second complexing agent and the third complexing agent are the same or different, and are independently selected from one or more of citric acid, tartaric acid, malic acid, succinic acid, sodium citrate, sodium tartrate, sodium malate and sodium succinate; Preferably, the molar ratio of the first complexing agent to the iridium source is 1.5 to 2:1, preferably 1.6 to 1.8:1; Preferably, the molar ratio of the second complexing agent to the ruthenium source calculated as ruthenium is 1 to 2:1, preferably 1.3 to 1.6:1; Preferably, the molar ratio of the third complexing agent to the titanium source is 1.5 to 3:1, preferably 2 to 2.5:

1.

10. The method according to claim 6, wherein: In step S1, the molar ratio of the iridium source calculated as iridium, the titanium source calculated as titanium, and the ruthenium source calculated as ruthenium is (2-5):(1.5-5):

1.

11. The method according to claim 6, wherein: The reaction conditions in step S1 include: temperature of 30 to 60° C., preferably 40 to 50° C.; reaction time of 1 to 4 hours, preferably 2 to 3 hours; Preferably, in step S1, the pH of the mixed material is 6 to 7; Optionally, a pH adjuster is added to adjust the pH; optionally, the pH adjuster is selected from one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide and ammonia water.

12. The method according to claim 6, wherein: In step S3, the conditions for the calcination treatment include: a calcination temperature of 350 to 450°C, preferably 380 to 400°C; and a calcination time of 2 to 5 hours, preferably 3 to 4 hours.

13. The method according to claim 6, wherein: The method further comprises: washing the product obtained by the roasting treatment; the solvent used in the washing treatment is a mixed solution of alcohol and water, and the alcohol accounts for 10 to 95% by weight of the mixed solution, preferably 30 to 60% by weight; Preferably, the alcohol is selected from one or more of methanol, ethanol, n-propanol and isopropanol.

14. The iridium, ruthenium and titanium composite catalyst prepared by the method according to any one of claims 6 to 13.

15. Use of the iridium, ruthenium and titanium composite catalyst according to any one of claims 1 to 5 and claim 14 in the production of hydrogen by electrolysis of water.